Introduction to mass communications - Agee, Warren Kendall; Ault , Phillip H.;Emery, Edwin (New York, NY : Harper & Row Publishers, Inc., 1988)
Since the first edition of this text helped shape the introductory mas communication course in scores of colleges and universities more than 25 years ago, the book has chronicled the evolving media scene.
Part One. The role of mass communications -- Part Two. The print media -- Part Three. The electronic and film media -- Part Four. The persuasive professions -- Part Five. Research and education -- Part Six. Criticisms and challenges.
Includes bibliographical references and index.
Keywords: MASS MEDIA